Perceived stigma among schizophrenia patients attending psychosocial rehabilitation in Kelantan - Rasdi, Normardhiah Md (2020)
Introduction: Stigma and discrimination cause significant burden within mental health care for people suffering from mental illness. Stigma in mental illness can be divided into social (public) stigma and personal stigma. Personal stigma can be further divided into perceived stigma and self-stigma. Schizophrenia is the most disabling mental illness and highly stigmatized all over the world. The evolution of psychosocial rehabilitation (PSR) for people with severe mental illness in Malaysia started since the early 20th century which focused on helping individual patients through psychological, social and occupational techniques. This study aimed to assess the level of perceived stigma among schizophrenia patients attending psychosocial rehabilitation in Kelantan and the association between perceived stigma level with sociodemographic factors, clinical features and psychosocial function. Methods: This was a cross-sectional study where 90 schizophrenia patients attending PSR in Kelantan were assessed using the Devaluation-Discrimination Scale-Malay version (DDS-M), the Brief Psychiatric Rating Scale-Extended version (BPRS-E) and The Personal and Social Performance Scale (PSP). The sample was randomly collected and analyzed for the association between level of perceived stigma and associated factors through simple linear regression (SLR) for initial screening then confirmed with multiple linear regression (MLR). Results: The mean score for the DDS-M was 2.70 (SD 0.388). Among the 90 patients, 59 had stigma score above the midpoint; while 31 scored below the mid-point. The results showed perceived stigma was negatively associated with age and depressive symptom, while positively associated with employment status history before attending PSR (p-value 0.012, 0.011 and 0.028 respectively). Conclusion: Perceived stigma among schizophrenia patients attending psychosocial rehabilitation in Kelantan was high and associated with age, employment status history before attending PSR and depressive symptom. Further therapeutic interventional program is needed to target personal stigma such as Cognitive Behavioral Therapy (CBT), coping skill on stigma and job coaching.